The complete Py)thon hacking course. (Manning Publications, 2023)
Master ethical hacking while working on practical Python coding projects. Learn Python hacking skills, ethical hacking principles, penetration testing, cybersecurity, and more with over 17 hours of video tutorials. Designed for those with intermediate- to advanced-level understanding of ethical hacking, this course is still taught in a step-by-step, beginner-friendly method. We begin with coding basic port and vulnerability scanning tools; move onto SSH, FTP, and spoofing attacks; take a look at network analysis; and finish up with coding a reverse shell, command and control center, and several website penetration testing tools. Upon completing this course, you will be prepared for a job in the cybersecurity industry. Learn all these skills while completing eight coding projects: Port and vulnerability scanner SSH brute-forcer MAC address changer ARP spoofer DNS spoofer Multi-functioning reverse shell Keylogger Command and control center.